2012
DOI: 10.1098/rstb.2011.0346
|View full text |Cite
|
Sign up to set email alerts
|

Climate change effects on above- and below-ground interactions in a dryland ecosystem

Abstract: Individual species respond to climate change by altering their abundance, distribution and phenology. Less is known, however, about how climate change affects multitrophic interactions, and its consequences for food-web dynamics. Here, we investigate the effect of future changes in rainfall patterns on detritivore-plant -herbivore interactions in a semiarid region in southern Spain by experimentally manipulating rainfall intensity and frequency during late spring -early summer. Our results show that rain inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 71 publications
(116 reference statements)
2
23
0
Order By: Relevance
“…Changes in above and belowground plant defences because of abiotic stress and/or interacting abiotic and biotic stress responses are of significant ecological relevance (Bezemer & van Dam 2005;Chakraborty & Newton 2011;Gonzalez-Megias & Menendez 2012;de Sassi & Tylianakis 2012). It is becoming more and more evident that the physical and physiological responses of plants to above and belowground stressors can ultimately impact multiple trophic levels and the entire ecosystem (Van Der Putten 2003;De Deyn & Van der Putten 2005;Kaplan et al 2008;van Dam 2009;Erb et al 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in above and belowground plant defences because of abiotic stress and/or interacting abiotic and biotic stress responses are of significant ecological relevance (Bezemer & van Dam 2005;Chakraborty & Newton 2011;Gonzalez-Megias & Menendez 2012;de Sassi & Tylianakis 2012). It is becoming more and more evident that the physical and physiological responses of plants to above and belowground stressors can ultimately impact multiple trophic levels and the entire ecosystem (Van Der Putten 2003;De Deyn & Van der Putten 2005;Kaplan et al 2008;van Dam 2009;Erb et al 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments and syntheses conducted in recent years have projected modifications and disruptions in species and multi-trophic interactions in drylands [61,68]. The complexities in the responses of organisms to global change challenge the establishment of general predictions.…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 99%
“…Here, we emphasize the important research gaps in our knowledge on how dryland trophic interactions might be affected by global change. González-Megías & Menéndez [68] evaluated the effect of future changes in rainfall patterns on detritivore-plant-herbivore interactions in a semi-arid region from Spain. The authors found that changes in rainfall intensity modified the effect of below-ground detritivores on both plant traits and above-ground herbivore abundance.…”
Section: Research Gaps and Future Directionsmentioning
confidence: 99%
“…However, understanding and predicting how biotic interactions will respond to climate change remains a great challenge (Tylianakis et al 2008, Barnett and Facey 2016), since both disrupting (Durant et al 2007, Memmott et al 2007, Singer and Parmesan 2010) and strengthening effects of climate change on species interactions have been observed (O'Connor 2009). This variety of results arises partly since responses to climate change differ between trophic levels (Voigt et al 2003, Tylianakis et al 2008, González‐Megías and Menéndez 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the Moricandia moricandioides system, a Brassicaceae herb inhabiting semiarid environments, root herbivory has been shown to modulate induced plant defenses and the interaction between the plant and aboveground organisms (González‐Megías and Müller 2010). In addition, shifts in rainfall patterns in this system have been shown to provoke changes in the strength and/or the sign of the interactions between below‐ and aboveground organisms, for example, disrupting the positive effect of detritivores on the abundance of chewing and sucking insects (González‐Megías and Menéndez 2012). In the present study, we focus on understanding the impact of changes in rainfall patterns on the interactions between root herbivores, its host plant, and its associated aboveground herbivorous insects.…”
Section: Introductionmentioning
confidence: 99%